Kemampuan Menulis Teks Cerpen Mahasiswa Program Sarjana Pendidikan Bahasa Indonesia - Agus Joko Purwadi; Didi Yulistio (LP4MK STKIP PGRI Lubuklinggau, 2021)
The purpose of this study was to describe the ability to write short story texts for students of the Indonesian Language Education Study Program, Faculty of Teacher Training and Education, Bengkulu University. The scope of this research covers aspects of (1) the relevance of the content to the theme, (2) the structure of the text, (3) the choice of words (diction), (4) narrative style sentences, and (5) mechanics. This study uses a descriptive method and a simple quantitative approach. The data collection used a short story writing test technique. The research sample used a purposive sampling technique, namely 33 students in the 5C semester of S-1 Indonesian Language Education Study Program, Department of Language and Arts Education, FKIP Bengkulu University. Data analysis used the mean formula and qualitative final analysis. The results of the study showed that the ability to write short stories for undergraduate students of Indonesian Language Education FKIP Bengkulu University was categorized as good (mean score 81.68). That is, students already have adequate skills in writing short stories although they still need to be improved in order to achieve maximum results. In particular, the ability to write short stories in four aspects has been achieved in good categories, namely (1) the suitability of the theme with the content, (2) the structure of the text, (3) the accuracy of word choice of diction, and (4) the mechanical aspects or spelling of Indonesian, and (5) aspects of narrative style sentences are categorized as very good. As for the contribution of each aspect to students' short story writing skills, namely the contribution of aspects (a) structure of 29.26%, (b) narrative style sentences of 21.33%, (c) relevance of theme to content of 20.14%, ( d) diction or word choice by 19.81%, and (e) mechanics by 9.45%. Meanwhile, the highest contribution was obtained from the aspect of the structure of the text.